Synthesis, And Physico-Chemical and Biological Charaterization of New Schiff Bases Derived From Thiophene and Their Transition Metal Complexes - Osman, Md.Uwaisulqarni (2007)
Several new Schiff bases formed from S-benzyldithiocarbazate (SBDTC) and S- methyldithiocarbazate (SMDTC) with selected aldehyde/ketones containing a thiophene ring namely, 1-(2-thienyl)-1-propanone and thiophene-2-carbaldehyde in 95 % of ethanol have been synthesized. Complexes of Cobalt(III), Nickel(II), Copper(II), Zinc(II) and Cadmium(II) with these Schiff bases were prepared. These compounds were characterized by elemental analyses and various physico-chemical techniques. Their thermal behaviour was also investigated. Single crystal X-ray analysis was carried out on nine single crystals. The Co(III) complexes are six-coordinated whereas, Ni(II), Zn(II) and Cd(II) complexes are four-coordinated. Unfortunately, none of the Cu(II) complexes produced single crystals but, it is proposed, that they are also four-coordinated. The Schiff bases and their metal complexes were evaluated for their cytotoxic and antimicrobial activities. Cytotoxic screening was carried out against Human ovarian cancer cells (CaOV-3), Human breast carcinoma cells with negative estrogen receptor (MDA-MB-231) and Human liver carcinoma cells (HEP-G2). Antimicrobial screening was carried out against four bacteria and three fungi. All compounds were found to have low or no activity except for Cu(SBT2P)2. H2O which is active against Bacillus subtilis-wild type (B29).